2015
DOI: 10.3329/bjdre.v5i1.22452
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status among Drug Addicts in a Selected Hospital in Dhaka City

Abstract: This was a cross-sectional study on oral health status of drug addicted patients admitted in a drug abuse treatment center in Dhaka city. This study was conducted at Mukti Mental Hospital, Drug & Alcohol Treatment Center situated at Gulshan, Dhaka, Bangladesh. The study was carried out among 50 drug addicts from the month of January to June 2012. Data were collected from the patients from 21st April to 5th May 2012. The main objective of the study was to assess and investigate the oral hygiene practice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This study results are consistent with related studies carried out in Nigeria, Jordan, Ghana, and Tanzania which also reported S. aureus mean CFU/mL within acceptable limits (Na'was et al, 1990;Tukur et al, 2012;Mugoyela and Mwambete, 2010;Opoku and Nyanor, 2019). A very high S. aureus contamination prevalence of 75% was reported by a study by Mamun et al in Dhaka city, Bangladesh, on cough syrups (Mamun et al, 2014). This could indicate possible extensive cross-contamination during the manufacture and storage of the syrups considered in the Dhaka study.…”
Section: Figuresupporting
confidence: 92%
See 3 more Smart Citations
“…This study results are consistent with related studies carried out in Nigeria, Jordan, Ghana, and Tanzania which also reported S. aureus mean CFU/mL within acceptable limits (Na'was et al, 1990;Tukur et al, 2012;Mugoyela and Mwambete, 2010;Opoku and Nyanor, 2019). A very high S. aureus contamination prevalence of 75% was reported by a study by Mamun et al in Dhaka city, Bangladesh, on cough syrups (Mamun et al, 2014). This could indicate possible extensive cross-contamination during the manufacture and storage of the syrups considered in the Dhaka study.…”
Section: Figuresupporting
confidence: 92%
“…Three brands; DS, K, and Z were easily complaint with BP requirements for microbiological quality for E. coli while brand P was barely compliant as the CFU/mL were at the upper acceptance limit. The presence of E. coli in cough syrups has also been reported in other studies carried out in Bangladesh (Mamun et al, 2014) and Nigeria (Mamun et al, 2014;Ibezim et al, 2018) where levels of 17% and 22% respectively were observed in the samples. However, the prevalence of E. coli contamination in this study was lower than that reported by both Mamun et al in Dhaka and Ibezim et al in Port Harcourt. Non-aqueous and aqueous pharmaceutical preparations for oral use should not contain E. coli as per the BP microbiological quality requirements for pharmaceuticals.…”
Section: Figuresupporting
confidence: 78%
See 2 more Smart Citations